Peramalan Penjualan Produk Teralis Besi Menggunakan Metode ARIMA: Studi Kasus Bengkel Las Bale Karya - Purnama, Indra; Waafi, M. Shane; Dwicahyo, Rikho Ardiyan; Al-Faritsy, Ari Zaqi (Lembaga Yasin AlSys, 2024)
Bengkel Las Bale Karya is one of the small and medium-sized enterprises (SMEs) that produces various types of iron crafts such as seesaws, swings, staircase railings, balcony railings, spiral staircases, iron doors, grilles, fence doors, and others. This research focuses on the production of iron grille products. The research method employed in this study is the ARIMA method for forecasting over the next 12 periods. The results of this study aim to optimize iron grille production to prevent product stockpiling, ensure material availability, and enhance workplace safety.